TRANSPARANSI PEREKRUTAN APARAT DI DESA PILOLALENGA KECAMATAN DUNGALIYO KABUPATEN GORONTALO - Sri Lestari Gintulangi (Universitas Muhammadiyah Gorontalo, 2018)
This study aims to determine the recruitment of village officials in Pilolalenga Village, Dungaliyo District, Gorontalo Regency. The method used in this research is descriptive qualitative. The results showed that of the five indicators measured namely guaranteed access as clear and accurate information, freedom for everyone to obtain information, governance, information about policy making, implementation and the results achieved have not shown the existence of a transparent village apparatus recruitment system related to the time details, terms and conditions of the recruitment process for village officials. This can be seen from the limited community access to obtain clear information related to the implementation of village apparatus recruitment so that the implementation of village apparatus recruitment is only followed by a small portion of the community. Keywords: Transparency, Recruitment of Village Officials